Formed articles
By incorporating bisamide additives into a blend composition with partially neutralized ethylene (meth)acrylic acid copolymers, the heat resistance of molded articles is enhanced, addressing the limitations of existing ionomers in high-temperature applications without compromising transparency and haze.
Patent Information
- Application Number
- JP2024561614
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-05-05
- Publication Date
- 2025-05-02
AI Technical Summary
Existing ionomers have insufficient heat resistance due to low melting temperatures and ion hopping, limiting their application in high-temperature environments without compromising other desirable properties like clarity and scratch resistance.
A blend composition comprising partially neutralized ethylene (meth)acrylic acid copolymers and bisamide additives, which improves the heat resistance of molded articles by enhancing the VICAT softening point and maintaining transparency and haze.
The addition of bisamide additives to ionomers significantly improves the heat resistance of molded articles, as evidenced by increased VICAT softening points and improved dimensional stability and creep resistance at high temperatures, while preserving transparency and haze.
Smart Images

Figure 2025514056000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to molded articles having improved heat resistance, and more particularly to molded articles made from a blend composition of (a) a partially neutralized ethylene (meth)acrylic acid copolymer and (b) a bisamide additive, wherein the resulting molded article made from the blend composition exhibits a percent improvement in a property, such as VICAT softening point, compared to a resulting molded article made from a blend composition comprising a partially neutralized ethylene (meth)acrylic acid copolymer that does not contain a bisamide additive. [Background technology]
[0002] Partially neutralized ethylene (meth)acrylic acid copolymers are known ionomers. These types of ionomers have several advantageous properties, including, for example, clarity, scratch resistance, oil resistance, high hot tack over a wide range, stiffness, thermoformability, puncture resistance, and seal through contamination. These types of ionomers are used in a variety of high-end applications, such as bottle caps for luxury perfumes, covers for golf balls, sealant layers for packaging films, shrink and skin packaging, shells for bowling pins, protective capping layers for wood-plastic composites, and lamination layers for architectural laminated glass. Despite having good properties, many ionomers have poor heat resistance due to the low melting temperature of small semi-crystalline ionomers and ion hopping of ion clusters. Creep and dimensional change at high temperatures are two examples of phenomena that limit the use of ionomers in a wider range of applications. Improving the heat resistance of ionomers is desirable to open new applications such as mobile phone protective cases, eyewear, transparent non-slip for footwear, building integrated photovoltaic encapsulation, household / kitchen utensils, etc. For example, in the mobile phone case manufacturing industry, mobile phone cases typically include thin-walled flexible regions made from thermoplastic polyurethane (TPU). Compared to TPU, ionomers have several advantages including transparency, gloss, yellowing resistance, and color relocation. However, one disadvantageous issue of known ionomers relates to their dimensional stability at high temperatures (e.g., >65°C). Therefore, it is desirable to improve the overall heat resistance of ionomers to provide the possibility of using ionomers in a wider range of applications. The improvement of the overall heat resistance of ionomers can be demonstrated by measuring the heat distortion temperature (HDT), VICAT softening point, creep, and dimensional stability of the ionomers. It is also desirable to improve the heat resistance of ionomers while retaining and maintaining the other advantageous properties of ionomers, such as clarity, scratch resistance, etc.
[0003] For example, there has been some success in improving the heat resistance of ionomers by using annealing processes, blends of polymer resins such as high-density polyethylene (HDPE), nylon, and polypropylene (PP), and crosslinking methods. For example, WO2021041618 mentions the use of blends of (1) ionomers and (2) isotactic polypropylene homopolymer (iPP) polymer resins to improve the heat resistance (e.g., HDT, stiffness, creep) of ionomers while maintaining the desired transparency. In the above references, 1% to 40% polyisopropylene (iPP) (or EP-iPP diblock copolymer or EP, (EP refers to a copolymer of ethylene and propylene)), 60% to 99% by weight of ionomers such as partially neutralized ethylene (meth)acrylic acid copolymers are used. The above references do not mention blending additives with the ionomers to improve the heat resistance of the resulting molded articles made from the blends.
[0004] Application Publication Nos. 2009291973 and 2009291974 refer to laminated films containing (1) ethylene methacrylic acid (EMAA) ionomers and (2) slip agents. The slip agents mentioned in the references include, among others, N-oleyl palmitamide and the monoamide behenic acid amide. The references are silent about improving the heat resistance of the laminated films or ionomers. However, it has been found that the monoamides do not help improve the heat resistance of the ionomers.
[0005] US Patent Publication No. 20090123613 refers to a multilayer packaging film or sheet comprising at least one layer, the layer being made from (1) an EMAA ionomer (a magnesium neutralized ionomer) and (2) a polyamide, a barrier resin (e.g., ethylene vinyl alcohol copolymer, EVOH), a polyolefin, a vinyl ester (e.g., ethylene-vinyl acetate, EVA), or a combination of two or more of these. Some of the specific polyamides mentioned in the above reference include various nylons. The blend compositions mentioned in the above reference relate to magnesium neutralized ionomers blended with other polymeric resins including polyamides, EVOH, EVA, and polyolefins. The above reference does not mention additives blended with the ionomer to improve the heat resistance of the resulting molded article made from the blend composition. Instead, the objectives described in the above reference are directed to improving the stiffness and rigidity of ionomers containing high levels of softening comonomers.
[0006] As explained by the above references, improving the heat resistance of ionomers is a challenge for the industry to achieve. For example, previous attempts to improve the heat resistance of ionomers have been found to impair at least one or more of the desired performance properties of ionomers, such as transparency, processability, and productivity. It would be beneficial to the industry to provide ionomers with some improvement in at least one or more of the ionomer properties at high temperatures. For example, improving the dimensional stability of ionomers at high temperatures (e.g., 65°C or higher) while retaining the transparency and flowability of the ionomers may enable the ionomers to be used in applications such as the manufacture of cell phone cases and eyewear (e.g., sunglasses). Also, improving the creep resistance properties of ionomers at 70°C without impairing the transparency properties of the ionomers may help reduce the return rate of products that are not acceptable to consumers, such as perfume caps. Therefore, it is desirable to provide an ionomer blend composition for use in the manufacture of molded articles with improved heat resistance while maintaining other beneficial properties of ionomers, such as transparency, scratch resistance, etc. Summary of the Invention
[0007] In one embodiment, the present invention relates to a molded article made from a composition comprising a blend of (a) at least one partially neutralized ethylene (meth)acrylic acid copolymer and (b) at least one bisamide additive, the blend composition being useful for making molded articles exhibiting a percent improvement in heat resistance. In another embodiment, the acid content of the partially neutralized ethylene (meth)acrylic acid copolymer (ionomer) is between 5 weight percent acid and 30 weight percent acid. In yet another embodiment, the neutralization level of the ionomer is 10 weight percent or more.
[0008] In yet another embodiment, the present invention provides a process for producing a molded article having improved heat resistance, comprising the steps of: (I) weighing the following ingredients to form a mixture: (a) at least one partially neutralized ethylene (meth)acrylic acid copolymer, the acid content being between 5 weight percent acid and 30 weight percent acid; and (b) at least one bisamide; (II) melt mixing or melt blending the components of step (I) at a predetermined temperature for a predetermined period of time to form a melt blend composition; and (III) forming the molten blend composition obtained in step (II) into a molded shape by compression molding or injection molding; Including, relating to a process.
[0009] In a preferred embodiment, the at least one bisamide has the following general chemical structure (I):
[0010] [ka] wherein R1 and R2 are independently selected from saturated alkyl groups having C1 to C30 carbon atoms, and R3 and R4 are independently selected from hydrogen or alkyl groups having C1 to C4 carbon atoms. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Temperatures used herein are in degrees Celsius (°C).
[0012] Unless otherwise specified, "room temperature (RT)" and / or "ambient temperature" herein means a temperature between 20°C and 26°C.
[0013] As used herein, the term "composition" refers to a mixture of materials that comprise the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0014] The term "polymer" refers to a polymeric compound prepared by polymerizing monomers, whether of the same or different types. Thus, the generic term polymer encompasses the term "homopolymer," which generally refers to a polymer prepared from only one type of monomer.
[0015] By "copolymer" herein is meant a polymer prepared from two or more types of monomers.
[0016] A "dipolymer" is a copolymer having two types of monomers.
[0017] A "terpolymer" is a copolymer having three different types of monomers.
[0018] With respect to the above terms copolymer, dipolymer, and terpolymer, the copolymer may be described herein in terms of its constituent comonomers or the amounts of its constituent comonomers, for example, a copolymer may be referred to as "a copolymer comprising ethylene and 18 weight percent acrylic acid," or a similar description.
[0019] "Ionomer" herein means an ionic partially neutralized derivative of a precursor acid copolymer. "Ionomer" is used interchangeably herein with "partially neutralized ethylene (meth)acrylic acid copolymer." Ionomers can be produced by neutralizing the unsaturated acid groups of a precursor acid copolymer with a reactant that is a source of metal ions in an amount such that neutralization of a certain percentage of the acid groups in the precursor occurs, based on the total acid group content of the precursor acid copolymer. "Ionomer" or "partially neutralized ethylene acid copolymer" can include, for example, ionomers where the acid groups of the ionomer are "(meth)acrylic acid," and the term "(meth)acrylic acid copolymer" herein means acrylic acid, methacrylic acid, or a mixture thereof.
[0020] For example, neutralization of the carboxylic acid groups of the precursor acid copolymer can be accomplished by treating the precursor acid copolymer with a base, such as sodium hydroxide, potassium hydroxide, zinc oxide, and the like. For example, the ethylene (meth)acrylic acid precursor copolymer is "partially neutralized" herein means that the carboxylic acid groups of the precursor ethylene (meth)acrylic acid copolymer are stoichiometrically less than 100 percent neutralized. For example, ionomers useful in the present invention include those available under the trade name SURLYN™ from The Dow Chemical Company.
[0021] The term "crystalline" refers to a polymer or polymer block that possesses a first order transition or crystalline melting point (Tm) as determined by differential scanning calorimetry (DSC) or equivalent technique. The term "crystalline" may be used interchangeably with the term "semi-crystalline."
[0022] The terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not they are specifically disclosed herein. For the avoidance of any doubt, all compositions claimed through the use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or not, unless stated to the contrary. In contrast, the term "consisting essentially of" excludes from the scope of any preceding description any other component, step, or procedure, except those that are not essential to operability. The term "consisting of" excludes any component, step, or procedure not specifically delineated or listed. The term "or" refers to the listed members individually and in any combination, unless otherwise stated. The use of the singular includes the use of the plural, and vice versa.
[0023] Numerical ranges disclosed herein include all values between the lower limit and the upper limit (inclusive). In the case of ranges containing explicit values (e.g., ranges 1, or 2, or 3-5, or 6, or 7), any subranges between any two explicit values are included (e.g., the range 1-7 above includes the subranges 1-2, 2-6, 5-7, 3-7, 5-6, etc.).
[0024] As used throughout this specification, the following abbreviations have the following meanings unless the context clearly dictates otherwise: "=" means "equal to" or "equal to", "<" means "less than", ">" means "greater than", "≦" means "less than or equal to", "≧" means "greater than or equal to", "@" means "at", ppm = parts per million, ppb = parts per billion, ppt = parts per trillion, "BV / hr" = bed volume per hour, "MT" = metric ton, g = grams, mg = milligrams, Kg = kilogram, L = liter, g / L = grams per liter, μL = microliter, "g / cm 3 " or "g / cc" = grams per cubic centimeter, g / 10min = grams per 10 minutes, mg / mL = milligrams per milliliter, "kg / m 3 = kilograms per cubic meter, ppm = parts per million by weight, pbw = parts by weight, rpm = revolutions per minute, m = meters, mm = millimeters, cm = centimeters, μm = microns or micrometers, nm = nanometers, min = minutes, s = seconds, ms = milliseconds, hr = hours, Pa = pascals, MPa = megapascals, Pa s = pascal seconds, mPa s = millipascal seconds, g / mol = grams per mole, g / eq = grams per equivalent, M n = number average molecular weight, M w = weight average molecular weight, pts = parts by weight, 1 / s or seconds -1 = reciprocal of seconds [s -1 ], °C = degrees Celsius, °C / min = degrees Celsius per minute, psi = pounds per square inch, kPa = kilopascals, % = percent, vol% = volume percent, mol% = mole percent, and wt% = weight percent.
[0025] Specific embodiments of the present invention are described herein below. These embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the inventive subject matter to those skilled in the art.
[0026] Unless otherwise stated, implied from the context, or customary in the art, all percentages, parts, ratios, and similar amounts are by weight, all temperatures are in degrees Celsius, and all test methods are current as of the filing date of this disclosure.
[0027] In general, the improved heat resistance molded article of the present invention is produced from a blend composition comprising (a) at least one partially neutralized ethylene (meth)acrylic acid copolymer (ionomer), the ionomer having an acid content of 5 weight percent acid to 30 weight percent acid and / or a neutralization level of 10 weight percent or more, and (b) at least one bisamide, the molded article exhibiting an improved ratio of properties, particularly improved heat resistance. If desired, other optional additives or agents, or compounds, optional component (c), may be added to the composition of components (a) and (b) above, provided that the optional components do not adversely affect the improved properties, such as heat resistance or other beneficial properties, of the final blend composition.
[0028] Component (a) of the blend formulation or composition for preparing the shaped article of the present invention is at least one partially neutralized ethylene (meth)acrylic acid copolymer or ionomer, the ionomer containing sodium ions (Na + ) neutralization, zinc ion (Zn 2+ ) or other neutralizing ions, such as calcium ions (Ca 2+ ), lithium ion (Li + ), aluminum ion (Al 3+ ), scandium ion (Sc 3+ ), iron ions (e.g., Fe 2+ and Fe 3+ ), yttrium ion (Y 3+ ), titanium ion (Ti4+ ), zirconium ion (Zr 4+ ), hafnium ion (Hf 4+ ), vanadium ions (e.g., V 2+ , V 3+ , V 4+ , and V 5+ ), cerium ions (e.g. Ce 3+ and Ce 4+ ), and magnesium ions (Mg 2+ ), as well as mixtures thereof to form ionomers. The ionomers of the present invention can be prepared by standard neutralization techniques known in the art.
[0029] In some embodiments, the total neutralization of the ionomer can be at least 1% or more up to 100%. In preferred embodiments, the ionomer is partially neutralized. By "partially neutralized" it is meant that the neutralization of the ionomer is, for example, at least 1% or more to 90%. In other embodiments, the total neutralization of the ionomer is 5% to 90% in one embodiment, 10% to 70% in another embodiment, and 20% to 65% in yet another embodiment. It is known that a neutralization level of the ionomer less than 1% can lead to reduced ionomeric properties, and a neutralization level of the ionomer greater than 90% can produce ionomers with poor flow properties. The metal ion used can be any metal ion in Group I or Group II of the Periodic Table of Chemical Elements. In some preferred embodiments, the metal ion is sodium, zinc, lithium, magnesium, calcium, or a mixture of any of these metal ions. In one preferred embodiment, sodium, zinc, lithium, magnesium, and mixtures thereof are used.
[0030] In some embodiments, the ionomers useful in the present invention have an ethylene (meth)acrylic acid content of at least 80% by weight or greater, and a melt index (MI, tested at 190° C. and 2.16 kg) of at least 0.1 g / 10 min or greater. For example, in some embodiments, the ionomers of the present invention have an ethylene (meth)acrylic acid content of 80% to 99% by weight in one typical embodiment, 85% to 99% by weight in another embodiment, and 90% to 99% by weight in yet another embodiment.
[0031] In some embodiments, the resulting ionomers used to make the blend compositions useful in the present invention may have a MI of 0.01 grams per 10 minutes (g / 10 min) to 100 g / 10 min in one typical embodiment, 0.1 g / 10 min to 50.0 g / 10 min in another embodiment, and 0.1 g / 10 min to 30 g / 10 min in yet another embodiment. The MI of the ionomers can be determined by the procedure set forth in ASTM D123 8 (at 190° C. and 2.16 Kg).
[0032] In other embodiments, some of the other advantageous properties of the ionomers include, for example, a suitable VICAT softening point as determined by the method described in ASTM D1525 at a heating rate of 50° C. / hr, a suitable heat distortion temperature (HDT) as determined by the method described in ASTM D648 at a heating rate of 120° C. / hr, a suitable transparency and haze as determined by the method described in ASTM D1003 Procedure A, and a suitable creep resistance and dimensional stability as determined by the methods described below in the present invention.
[0033] Creep resistance test Before testing the samples, store the samples in a desiccator box (humidity 25% and room temperature about 24°C) for 3 weeks. Cut the samples to a size of 40 mm x 12.7 mm x 2 mm. Creep resistance tests are carried out in torsion mode by a rheometer (ARES-G2, available from TA instruments). The sample length between the two torsion fixtures is 30 mm. The test characteristics of the samples include temperature of 70°C, angular frequency of 10 rad / s, strain of 0.01% to about 1%, creep of 0.6 MPa, 7200 s, and recovery of 0 Pa, 7200 s.
[0034] Dimensional Stability Test Before testing the ionomer samples, they are stored in a desiccator box (25% humidity and room temperature of about 24°C) for 3 weeks. The samples are 120mm x 10mm x 4mm in size. Before heating the samples, the original length of the samples (defined as L0) is measured using a vernier caliper. The ionomer samples are then heated in an oven at high temperature (e.g., 60°C or 70°C) for 3 days and then for an additional 7 days. The length of each sample is then re-measured on the 3rd and 7th days (defined as "L0"). 加熱後 "), and the "% Change" of each sample is calculated using the following formula, which is formula (IV) in the Examples: % Change = (L 加熱後 -L0) / L0. If desired, other methods known to those skilled in the art can be used to determine the above properties of an ionomer.
[0035] Examples of ethylene (meth)acrylic acid copolymers or ionomers useful in the present invention include ethylene methacrylic acid (EMAA), ethylene acrylic acid (EAA), and mixtures thereof. In some preferred embodiments, the ionomers used in the present invention may be partially neutralized. The ionomers of the present invention may include various grades of ionomers having different ranges of neutralization. For example, the ionomers may include a (meth)acrylic acid content of 5% acid to 30% acid by weight in one typical embodiment, 8% to 28% by weight in another embodiment, 9% acid to 25% by weight in yet another embodiment, and 10% acid to 20% by weight in yet another embodiment. The ionomer may also have a neutralization level ranging from 1% to 100% in one general embodiment, from 1% to 90% in another embodiment, from 5% to 90% in yet another embodiment, from 10% to 70% in yet another embodiment, from 20% to 70% in yet another embodiment, and from 20% to 65% in yet another embodiment. The acid may also be neutralized with Na+ or Zn+ ions. Thus, the ionomer used in the present invention may, for example, be selected from the group consisting of: an ionomer having 15% by weight acid, and ... + Ionomer that is 50% neutralized with ions, has 10% by weight acid, and has Na + Ionomer that is 55% neutralized with ions, has 15% by weight acid, and has Na + Ionomer that is 59% neutralized with ions, has 15% acid by weight, and Zn 2+ Ionomer that is 58% neutralized with ions, has 19% by weight acid, and has Na + Ionomers that are 45% neutralized with ions, and mixtures thereof.
[0036] In another embodiment, the ionomers used in the present invention to form the blend composition can include a mixture of (1) ethylene (meth)acrylic acid copolymers having various ranges of neutralization and (2) non-neutralized ethylene (meth)acrylic acid copolymers. The neutralization level of the ionomers present in the blend composition refers to the average stoichiometric neutralization of the carboxylic acid groups of the precursor ethylene (meth)acrylic acid copolymer mixture.
[0037] In one typical embodiment, the concentration of ionomer useful in preparing the blend composition can be from 80% to 99% by weight, in another embodiment from 85% to 98% by weight, and in yet another embodiment from 90% to 98.5% by weight, based on the total weight of all components in the composition. If the concentration of ionomer is greater than 99% by weight, the ionomer may exhibit a lower percentage improvement in heat resistance, and if the concentration of ionomer is less than 80% by weight, the clarity of the ionomer may be adversely affected.
[0038] Component (b) of the blend composition useful for preparing the molded articles of the present invention is at least one bisamide additive. In one typical embodiment, the bisamide additive has the following general chemical structure, Structure (I):
[0039] [ka] (wherein R1 and R2 are independently selected from saturated alkyl groups having C1 to C30 carbon atoms; R3 and R4 may be at least one bisamide having a substituent selected from hydrogen or an alkyl group having C1 to C4 carbon atoms.
[0040] Examples of the bisamide component (b) include ethylenebisstearamide (EBS), ethylenebislauramide (EBL), ethylenebisbehenamide (EBB), ethylenebisdecoylamide (EBD), ethylenebispelargonamide (EBP), ethylenebiscapramide (EBC), ethylenebisundecanoic amide (EBU), and mixtures thereof. In a preferred embodiment, the bisamide of the blend composition of the present invention comprises, consists essentially of, or consists of EBS, EBD, EBL, and mixtures thereof.
[0041] In some embodiments, the properties of the bisamide additive include, for example, a melting point greater than 130° C. as determined by differential scanning calorimeter (DSC).
[0042] The concentration of the bisamide additive useful in preparing the blend compositions of the present invention can be from 0.5% to 15% by weight in one typical embodiment, from 1% to 15% by weight in another embodiment, and from 2% to 10% by weight in yet another embodiment, based on the total weight of all components in the composition.
[0043] In addition to the above components (a) and (b), the blend composition of the present invention may be optionally formulated with a wide variety of additives to enable it to perform specific functions while maintaining the excellent advantages / properties of the blend composition of the present invention in order to produce molded articles with improved heat resistance.For example, the optional additive component (c) useful in the blend composition may be selected from the group consisting of colorants, pigments, carbon black, mineral fillers, process oils; flame retardants, foaming agents; processing aids, antioxidants, UV light stabilizers, scorch retarding additives, metal oxides, nucleating agents, and mixtures thereof.The additives may be formulated either in their original form or in the form of a masterbatch.
[0044] In other embodiments, the optional additives added to the blend composition can include one or more polymeric components of polypropylene, polyethylene, thermoplastic vulcanizates, ethylene propylene diene monomer, non-neutralized ethylene (meth)acrylic acid copolymers, ethylene acrylate copolymers (wherein the alkyl acrylate includes methyl acrylate, methacrylate, ethyl acrylate, or n-butyl acrylate, or isobutyl acrylate), and mixtures thereof.
[0045] The optional compounds, when used to prepare the blend compositions useful in the present invention, can generally be present in an amount ranging from 0% to 20% by weight in one embodiment, from 0.01% to 20% by weight in another embodiment, and from 0.1% to 20% by weight in yet another embodiment.
[0046] In one broad embodiment, a process for making a blend composition or formulation useful for making a molded article of the present invention comprises blending a polymerizable compound having the following general chemical structure, Structure (I):
[0047] [ka] (wherein R1 and R2 are independently selected from saturated alkyl groups having C1 to C30 carbon atoms; R3 and R4 are independently selected from hydrogen or an alkyl group having C1 to C4 carbon atoms.
[0048] The above mixture of components (a) and (b) may, if desired, contain one or more additional optional components, component (c). For example, components (a), (b), and optionally (c) may be mixed together in the desired concentrations described above. If desired, optional additive component (c) may be mixed with either one of components (a) and (b) or both components (a) and (b). The order of mixing the components is not important, and two or more components may be mixed together before adding the remaining components. The components of the formulation may be mixed together by any conventional mixing process and equipment known to those skilled in the art of mixing, for example, a twin-screw extruder. For example, when using a twin-screw extruder, the components may be mixed at temperatures in various zones of the extruder barrel, in one typical embodiment, at temperatures between 115°C and 190°C. Other characteristics of the twin-screw extruder used are known to those skilled in the art, such as the extruder output, the extruder diameter D, the extruder length / diameter (L / D) ratio, the temperatures in the various zones of the extruder barrel, the screw speed, and the total feed rate of the ingredients.
[0049] By way of illustration of the present invention and not by way of limitation, in one preferred embodiment, the temperatures of the various zones (e.g., six zones) of the extruder barrel may be as follows: 115°C / 145°C / 190°C / 190°C / 190°C / 180°C, the extruder screw speed may be set at 250 rpm, and the total feeding rate of the ingredients to the extruder may be 10 kg / hr.
[0050] The blended compositions comprising the ionomers and bisamides of the present invention produced by the above methods have several advantageous properties and / or benefits compared to known elastomer compositions. For example, the blended compositions of the present invention, when used to produce molded articles, can provide molded articles that exhibit a percent improvement in HDT at elevated temperatures (as measured by VICAT softening point (at 50° C. / hr 10 N)) compared to molded articles made from compositions comprising ionomers without the bisamide additive. In general, the HDT (at 120° C. / hr, 0.45 MPa) of the molded articles as measured by VICAT softening point can be increased by at least 3% in one embodiment, at least 5% in another embodiment, 5% to 50% in yet another embodiment, and 5% to 30% in yet another embodiment. In addition, molded articles made from the compositions of the present invention exhibit improved heat resistance while maintaining (retaining) other advantageous properties, such as good dimensional stability, low creep, good stiffness, low haze, clarity, scratch resistance, etc.
[0051] In some embodiments, the ionomer has a percent transparency (% transparency) of at least 80% in one typical embodiment, 80% to 99% in another, and 80% to 95% in yet another embodiment. In some embodiments, the ionomer has a percent haze of 1% to 25% in one typical embodiment, 1% to 20% in another, and 1% to 15% in yet another embodiment.
[0052] The blend compositions of the present invention can be used, for example, to fabricate various shapes, parts, products, or articles using molding processes. Other applications for the blend compositions and articles made therefrom include appliance applications, electronic product applications, protective case applications, home / kitchen applications, sporting goods applications, footwear, and packaging applications.
[0053] For example, in a broad embodiment, the process for making a molded article includes first making a blend composition useful in the present invention, and then using the blend composition to make a molded article. In some embodiments, the process for making a molded article includes: (I) weighing out the following components: (a) at least one partially neutralized ethylene (meth)acrylic acid copolymer described above, (b) at least one bisamide described above, and optionally (c) additional additives, as desired, to provide appropriate amounts of components (a), (b), and optionally (c); (II) melt mixing or melt blending the components of step (I) to form a mixture or blend composition; (III) molding the mixture or blend composition obtained from step (II) into a shaped shape by compression molding or injection molding; Includes.
[0054] In another embodiment, the process for producing the molded article comprises: (I) weighing out the following components: (a) at least one partially neutralized ethylene (meth)acrylic acid copolymer described above, (b) at least one bisamide described above, and optionally (c) additional additives, as desired, to provide appropriate amounts of components (a), (b), and optionally (c); (II) mixing or blending the components of step (I) at a predetermined temperature for a predetermined period of time to form a mixture or blend composition; (III) forming the mixture composition resulting from step (II) into the shape of a finished part or article, where the forming of the molded part or article occurs in a molding apparatus, such as by using compression molding or injection molding equipment and methods; (IV) cooling or allowing to cool the molded finished part or article from step (III) in the mold apparatus to a temperature sufficient to form a solid, handleable finished solid part or article; (V) removing the finished solid part or article of step (III) from the mold apparatus; Includes.
[0055] In some embodiments of the above process, the process condition(s) for carrying out the compounding step of step (II) of the above process include a melt temperature in the range of from 140°C to 280°C in one embodiment, and from 140°C to 260°C in another embodiment.
[0056] Compression molding and injection molding equipment and methods are known to those skilled in the art of molding. For example, in one typical embodiment, the conditions for carrying out the injection molding of the finished part or article in step (III), i.e., forming the mixed composition obtained from step (II) into the shape of the finished part or article, include, for example, the following steps: (1) melting the mixed composition at a processing temperature of 160°C to 250°C to form a molten composition, and then (2) injecting the molten composition into a cooler mold and holding it at a pressure of 20MPa to 200MPa for a certain period of time (fill time). The filling time of the molten polymer composition is 1 second to 30 seconds, and the mold temperature is 10°C to 50°C. Then, (3) removing the resulting molded article from the mold.
[0057] The above non-limiting processing temperature ranges for injection molding can vary depending on various parameters such as the particular ionomer selected, part specifications, and mold conditions (e.g., part thickness and size, mold gate size and location, etc.). For example, if an ionomer with a high MI (e.g., 3 g / 10 min or greater) is used and thick-walled (e.g., 4 mm or greater) parts are desired to be produced, lower processing temperatures such as 160°C to 200°C can be used. On the other hand, if an ionomer with a low MI (e.g., less than 3 g / 10 min) is used and thin-walled (e.g., less than 4 mm) parts are desired to be produced, higher processing temperatures such as 200°C to 250°C can be used.
[0058] In another typical embodiment, compression molding is carried out by (1) placing pellets of the polymer composition into a mold, (2) inserting the mold into a hot press, (3) holding the mold under pressure for a period of time at a melt temperature of 160° C. to 250° C., and then (4) cooling the mold and removing the resulting molded article from the mold.
[0059] For compression molding, the preset melt temperature for melting the polymer resin is generally set 20° C. higher than the actual melt temperature of the polymer resin, and the processing temperature may be in the range of 100° C. to 250° C. depending on the resin. For compression molding, the above non-limiting processing temperature range may also vary depending on various parameters such as the particular ionomer selected, part specifications, and mold conditions (e.g., part thickness and size, and mold gate size and location, etc.).
[0060] In some embodiments, the ionomer component (a) can be present in the blend composition at a concentration of 80% to 99% by weight to form a mixture or blend composition. In some embodiments, component (a) can have a (meth)acrylic acid content of 5% to 50% by weight, and component (a) can have a melt index of 0.01 g / 10 min to 100 g / 10 min. The bisamide additive can be present in the composition at a concentration of 1% or more to 10% by weight, for example to form a mixture or blend composition.
[0061] In another general embodiment, the bisamide additive can be compounded to form a masterbatch composition using an ionomer as a carrier resin, and the concentration of the bisamide used to form the masterbatch can be, for example, from 1% by weight or more to 70% by weight. The compounding process to form the masterbatch is to mix or blend the ionomer, bisamide, and any optional ingredients, if desired, to form a homogenous mixture. EXAMPLES
[0062] The following Inventive Examples (Inv. Ex.) and Comparative Examples (Comp. Ex.) (collectively "Examples") are presented herein to further illustrate the features of the present invention, but are not intended to be construed, either explicitly or implicitly, as limiting the scope of the claims. Inventive Examples are identified by Arabic numerals, and Comparative Examples are represented by alphabetical letters. The following experiments analyze the performance of embodiments of the compositions described herein. Unless otherwise indicated, all parts and percentages are by weight based on total weight.
[0063] Abbreviation Some of the names and abbreviations used for some of the materials and items used in the examples are as follows: "SA" stands for stearamide, which is a monoamide additive and is commercially available from SCRC. "BA" stands for behenamide, which is a monoamide additive and is commercially available from SCRC. "EBS" stands for ethylene bisstearamide, which is a laboratory sample of bisamide additive and is available from Sichuan Tianyu Oleochemical Co. Ltd. "EBO" stands for ethylene bisoleamide, a bisamide additive, commercially available from SCRC. "EBB" stands for ethylene bisbehenamide, a bisamide additive, commercially available from SCRC. "C6-Di" refers to adipic acid, which is a diacid and is commercially available from SCRC. "C12-Di" refers to dodecanedioic acid, which is a diacid and is commercially available from SCRC. "HDT" stands for heat distortion temperature. "MAA" stands for methacrylic acid.
[0064] raw materials Suitable ionomer components (raw materials; ingredients) used in the examples are set forth in Table I, and all ionomers are available from The Dow Chemical Company.
[0065] [Table 1]
[0066] Mixture composition The blend compositions used in the examples were prepared according to the following formulas set forth in Table II.
[0067] [Table 2]
[0068] General Procedure for the Blending Process The ionomer compound was in the form of pellets and the bisamide additive was in the form of powder. The ionomer and bisamide components were blended together by a twin screw extruder compounding process according to the loading settings listed in Table II above. The additive powder was fed into the extruder together with the ionomer pellets in a designed weight ratio, e.g., 1:19 (representing a 5 wt% loading), under the following extruder conditions:
[0069] The extruder equipment was a ZSK18 twin screw extruder with a power output of 19.2 KW, diameter (D) of 18 mm, and L / D of 48. The temperatures of the various zones of the extruder barrel were set at 115° C. / 145° C. / 190° C. / 190° C. / 190° C. / 180° C., the screw speed was set at 250 rpm, and the total feed rate of the ingredients was 10 kg / h.
[0070] General Procedure for the Injection Process The ionomer pellets were dried in a dehumidifier at 60° C. for at least 4 hours before feeding the pellets into the extruder for injection molding. The injection molding machine used in this process is called Fanuc Roboshot S-2000i100BH injection machine available from FANUC Corporation, and was used for injection molding to make samples for impact testing. The barrel temperature of the injection screw was set at 190° C., the cooling temperature was 20° C., and the cooling time was 15 seconds. The injection speed was set at 30 mm / s, and the injection pressure was 200 MPa. Two different sizes of test samples were made: (1) rectangular bar samples with dimensions of length (L)×width (W)×thickness (T): 120 mm×10 mm×4 mm, which were used for VICAT and dimensional stability tests, and (2) rectangular bar samples with dimensions of L×W×T: 60 mm×60 mm×2 mm, which were used for creep resistance tests. The samples used for the creep resistance test were further cut into samples having a size of 40 mm×12.7 mm×2 mm for creep resistance test.
[0071] Test Method VICAT softening point Prior to testing, the test samples (test specimens) were stored in a desiccator box (relative humidity [RH] 25% and room temperature [RT: about 24°C]) for 3 weeks. The test specimens were cut to a size of 10 mm x 10 mm x 4 mm for testing. The VICAT softening point of the test specimens was determined with a Ceast HDT.6.VICAT, a testing instrument available from Instron Corporation. A flat-tipped needle loaded with a specific mass is placed in direct contact with the test specimen. The mass applied is a 10 N load. The test specimen and needle are heated in a heat transfer medium at a rate of 50°C / hr. The temperature at which the needle penetrates to a depth of 1 mm is recorded as the VICAT softening point. The VICAT softening point test method used in this invention is described in ASTM D1525. The results are listed in Table III.
[0072] HDT Prior to testing, the samples were stored in a desiccator box (25% RH and RT) for 3 weeks. The sample size was 120 mm x 10 mm x 4 mm obtained from the injection molding process described above. The samples were tested in an instrument called Ceast HDT 6 VICAT available from Instron Corporation to obtain the HDT properties of the samples. Rectangular cross-section bars are tested in an edgewise position as simple beams with a load applied at the center of the bar to give a maximum fiber stress of 0.455 MPa [66 psi]. The specimen is immersed under load in a heat transfer medium with a means to increase the temperature at 2°C / min. The temperature of the medium is measured when the test bar is deflected 0.34 mm [0.010 in.]. This temperature is recorded as the deflection temperature of the specimen under bending load. The method used to determine the HDT of the samples is described in ASTM D648. The results are listed in Table III.
[0073] Transparency and Haze The test method used to obtain the sample clarity and haze properties was performed on an equipment called BYK Gardner haze-guard dual equipment available from BYK Instruments (Altana Group Corporation). The sample size for testing was 60 mm x 60 mm x 2 mm, which was obtained from the general procedure of injection molding described above. The method used to determine the sample clarity and haze is described in ASTM D1003 Procedure A. The results are listed in Table III.
[0074] The above test experiment includes two parts, namely, a light source part and a light trap part. The sample is placed in the middle of the two parts and the test results are recorded. The light intensity is collected and used to calculate the transmittance and haze. The general procedure includes the following steps: (1) measuring the background in air as 0% haze or 100% transmittance, (2) calibrating the test equipment (detector) by placing a black cover over the detector test window to block the light to the detector, and then measuring the transmittance and haze, which results in 0% transmittance (or 100% haze), and then (3) placing the sample in the middle between the above two parts to obtain the test results.
[0075] Melt Index The Melt Index (MI) reported in Table III is tested using the procedure set forth in ASTM D-1238 at 190° C. and a 2.16 Kg weight.
[0076] [Table 3] Notes to Table III: (1) "Transparent" = transparency.
[0077] To calculate the "%Δ" of the VICAT values listed in Table III above, the following formula (I) is used:
[0078]
number
[0079] To obtain %ΔVICAT values using formula (I), Inventive Example 1 is compared to Comparative Example A, Inventive Example 2 is compared to Comparative Example A, Inventive Example 3 is compared to Comparative Example G, Inventive Example 4 is compared to Comparative Example H, Inventive Example 5 is compared to Comparative Example I, and Inventive Example 6 is compared to Comparative Example J.
[0080] To calculate the "%Δ" haze values listed in Table III above, the following formula (II) is used:
[0081]
number
[0082] To obtain %Δ haze values using formula (II), Inventive Example 1 is compared to Comparative Example A, Inventive Example 2 is compared to Comparative Example A, Inventive Example 3 is compared to Comparative Example G, Inventive Example 4 is compared to Comparative Example H, Inventive Example 5 is compared to Comparative Example I, and Inventive Example 6 is compared to Comparative Example J.
[0083] Creep Resistance The samples tested for creep resistance were stored in a desiccator box (25% RH and RT) for 3 weeks before testing. The samples were cut to a size of 40 mm x 12.7 mm x 2 mm. The sample length between the two torsion fixtures was 30 mm. The creep resistance test was carried out by a rheometer, torsion fixture geometry called ARES-G2 available from TA instruments. The creep resistance test parameters were as follows: temperature was 70°C; angular frequency was 10 rad / sec; strain was 0.01% to about 1%; torsion after 7,200 s was 0.6 MPa. Recovery was 0 Pa at 7,200 s. The results are listed in Table IV.
[0084] [Table 4]
[0085] To calculate the "%Δ" creep resistance values listed in Table IV above, the following formula (III) is used:
[0086]
number
[0087] To obtain the %ΔCreep Resistance values using formula (III), Inventive Example 1 is compared to Comparative Example A, Inventive Example 2 is compared to Comparative Example A, Inventive Example 3 is compared to Comparative Example E, Inventive Example 4 is compared to Comparative Example F, Inventive Example 5 is compared to Comparative Example G, and Inventive Example 6 is compared to Comparative Example H.
[0088] Dimensional Stability Test Prior to testing, the slips of ionomer samples were stored in a dryer box (25% RH and RT) for 3 weeks. The slips were molded by the injection molding process described above. The slips were 120 mm x 10 mm x 4 mm in size. Before heating the slips, the original length of the slips was measured by a vernier caliper. The ionomer samples were heated in two different high temperature ovens, 60°C and 70°C, for 3 and 7 days, respectively. The slip length was measured on the 3rd and 7th day, and the percent change in slip length (% change) was calculated according to the following formula (IV):
[0089]
number
[0090] [Table 5]
[0091] Discussion of results VICAT softening point and HDT are two relevant properties that reflect the properties of heat resistance. Ionomers have lower VICAT softening point and HDT compared to other polyolefin resins due to the special structure of ion clusters and secondary crystallites of ionomers. The challenge is to improve the heat resistance of ionomers without compromising other important performance properties such as high transparency and low haze. In the present invention, bisamide additives are blended with ionomers, and the resulting blended composition has improved VICAT softening point while maintaining transparency and haze compared to the original ionomer. The data shown in Table III show that 5 wt% EBS or EBB improves VICAT by about 4°C to 11°C compared to the original ionomer.
[0092] The transparency and haze of the ionomers tested were maintained except for Ionomer 3, which contained only 10% MAA. Without being limited to any particular theory, it is theorized that the mechanism by which Ionomer 3 does not maintain transparency and haze is as follows: the crystallite size of EBS decreases as the bisamide groups form hydrogen bonds with the carboxyl groups. When the ionomer has a low % MAA, the hydrogen bonds are not strong enough to bind EBS to the carboxyl groups and any free EBS crystals grow to a larger size, which in turn strongly scatters light.
[0093] Two monoamides were investigated at a loading of 5 wt% based on the weight of all blend components. However, unlike the bisamide additive, no obvious change in VICAT properties was observed. Stearamide significantly decreased the HDT properties, but the transparency and haze were unchanged from the parent ionomer. A bisamide containing unsaturated alkyl chains (EBO) was also investigated. EBO gave less improvement in VICAT softening point compared to the saturated bisamide (EBS) since the double bonds on the alkyl chains impair the crystallinity of the bisamide.
[0094] Poor creep resistance at high temperatures is another problem of ionomers. The results in Table IV show that 5 wt% EBS additive could significantly improve the creep resistance of ionomers at 70°C. However, neither monoamide (SA) nor bisamide (EBO) with double bonds showed obvious changes in creep resistance properties. The creep resistance at 70°C was consistent with the VICAT softening point results, demonstrating that bisamide additive with saturated alkyl chains could improve the heat resistance of ionomers.
[0095] Additionally, dimensional stability at high temperatures is also a concern for ionomers. Even at 60°C or 70°C, obvious shape changes were observed in the ionomers. For example, Table V provides a comparison of Ionomer 5 without bisamide additive and Ionomer 5 with 5 wt% EBS additive. The results shown in Table V show that the dimensional stability of Ionomer 5 is improved by adding the EBS additive to the ionomer.
[0096] Overall, the long saturated alkyl chain bisamide additives, when used with ionomers, provide ionomers with significantly improved VICAT, creep resistance, and dimensional stability at high temperatures while maintaining the clarity and haze properties of the ionomer.
[0097] conclusion In the present invention, it has been unexpectedly found that blending a long alkyl chain bisamide additive into an ionomer improves the ionomer's properties such as VICAT softening point, dimensional stability at 60°C, and creep resistance at 70°C, while at the appropriate loading (e.g., 5 wt%), other properties of the ionomer such as transparency are maintained. When a monoamide, bisamide, or diacid is incorporated into an ionomer, the bisamide (e.g., EBS) shows improved heat performance of the ionomer while maintaining the transparency of the ionomer. The use of a monoamide (e.g., stearamide or behenamide) additive with an ionomer shows little or even a negative effect on VICAT, but transparency can be maintained. The diacid additive in the ionomer is not compatible with the ionomer, and the use of the diacid additive in the ionomer reduces the transparency or haze performance of the ionomer.
[0098] When an appropriate amount of EBS (e.g., 5 wt.% EBS) is used in several ionomers with different acids, neutralization ratios, and cation types, the ionomers all show significant improvement in VICAT softening point compared to the control ionomer while maintaining similar clarity or haze. Also, several ionomers of the present invention (containing 5 wt.% EBS) show significant improvement in both creep resistance and dimensional stability of the ionomer at high temperatures when compared to the control ionomer.
Claims
1. 1. A molded article having improved heat resistance, comprising: (a) 90 weight percent or more of at least one partially neutralized ethylene (meth)acrylic acid copolymer, the acid content being from 5 weight percent acid to 30 weight percent acid; and (b) 1 weight percent or more of the following general chemical structure: 【Chemistry 1】 (In the formula, R 1 and R 2 is independently selected from saturated alkyl groups having C1 to C30 carbon atoms; R 3 and R 4 are independently selected from hydrogen or an alkyl group having from C1 to C4 carbon atoms, Manufactured from a blend comprising the molded article exhibits a percent improvement in VICAT softening point of at least 3 percent compared to a partially neutralized ethylene (meth)acrylic acid copolymer not containing a bisamide additive; A molded article, wherein the molded article exhibits a percent difference in haze of 15 percent or less compared to a partially neutralized ethylene (meth)acrylic acid copolymer that does not contain a bisamide additive.
2. 10. The shaped article of claim 1, wherein the neutralization level of the partially neutralized ethylene (meth)acrylic acid copolymer is 10 weight percent or greater.
3. 2. The shaped article of claim 1, wherein the partially neutralized ethylene (meth)acrylic acid copolymer is ethylene methacrylic acid, ethylene acrylic acid, and mixtures thereof.
4. 10. The shaped article of claim 1, wherein the concentration of the partially neutralized ethylene (meth)acrylic acid copolymer is from 90 percent to 99 percent.
5. 2. The shaped article of claim 1, wherein the bisamide is ethylene bisstearamide, ethylene bislauramide, ethylene bisbehenamide, ethylene bisdecyl amide, ethylene bisperargonamide, ethylene biscapramide, ethylene bisdecanoic acid amide, and mixtures thereof.
6. 10. The shaped article of claim 1, wherein the concentration of the bisamide is from 1 weight percent to 10 weight percent.
7. 2. The shaped article of claim 1, wherein the partially neutralized ethylene (meth)acrylic acid copolymer is nominally neutralized with a salt containing an alkali metal cation, an alkaline earth metal cation, a transition metal cation, a rare earth metal cation, or a combination of two or more thereof.
8. 9. The shaped article of claim 8, wherein the neutralization ratio of the partially neutralized ethylene (meth)acrylic acid copolymer is from 10 percent to 90 percent.
9. 1. A process for producing a molded article having improved heat resistance, comprising: (I) weighing the following ingredients to form a blend or mixture: (a) 90 weight percent or more of at least one partially neutralized ethylene (meth)acrylic acid copolymer, the acid content being from 5 weight percent acid to 30 weight percent acid; and (b) 1 weight percent or more of the following structure: 【Chemistry 2】 (In the formula, R 1 and R 2 is independently selected from saturated alkyl groups having C1 to C30 carbon atoms; R 3 and R 4 are independently selected from hydrogen or an alkyl group having from C1 to C4 carbon atoms, (II) melt mixing or melt blending the components of step (I) at a predetermined temperature for a predetermined time to form a mixture composition; and (III) forming the mixture composition obtained from step (II) into a molded shape by compression molding or injection molding; The process includes:
10. 10. The process of claim 9, wherein the neutralization level of the at least one partially neutralized ethylene (meth)acrylic acid copolymer is 10 weight percent or greater.
11. 10. The process of claim 9, wherein step (II) of forming the mixed composition comprises extruding the partially neutralized ethylene (meth)acrylic acid copolymer from step (I) and the bisamide into the shape of a finished part or article.
12. 10. The process of claim 9, wherein step (II) comprises melt mixing or melt blending the components of step (I) at a predetermined temperature for a predetermined time to form a masterbatch composition, and step (III) comprises molding the masterbatch resulting from step (II) into a shaped shape by compression molding or injection molding.
13. 10. The process of claim 9, wherein step (II) of melt mixing or melt blending the components of step (I) is carried out using a mixing or blending device selected from the group consisting of a roll mill, an internal mixer, a single screw extruder, a twin screw compounding extruder, and combinations thereof.
14. 1. A process for producing a molded article having improved heat resistance, comprising: (a) 90 weight percent or more of a partially neutralized ethylene (meth)acrylic acid copolymer, the acid content being between 5 weight percent acid and 30 weight percent acid; and (b) 1 weight percent or more of the following structure: 【Chemistry 3】 (In the formula, R 1 and R 2 is independently selected from saturated alkyl groups having C1 to C30 carbon atoms; R 3 and R 4 are independently selected from hydrogen or an alkyl group having from C1 to C4 carbon atoms; forming a composition by blending the molded article exhibits a percent improvement in VICAT softening point of at least 3 percent compared to a partially neutralized ethylene (meth)acrylic acid copolymer containing no additive; The process wherein said molded article exhibits a percent difference in haze of 15 percent or less compared to a partially neutralized ethylene (meth)acrylic acid copolymer containing no additive.
15. 15. The process of claim 14, wherein the neutralization level of the partially neutralized ethylene (meth)acrylic acid copolymer is 10 weight percent or greater.
Citation Information
Patent Citations
JP1974018619A